ChemInform Abstract: Rapid Construction of Imidazopyridines from ortho‐Haloaminopyridines. Issue 41 (September 2016) - Li, Chaomin; Chen, Lily; Steinhuebel, Dietrich; Goodman, Andrew
Abstract: A two‐step C—N coupling/cyclization reaction sequence is developed for the synthesis of imidazopyridine derivatives.